Let's Work It Out (or We'll See You in Court): Litigation and Private Dispute Resolution in Vertical Exchange Relationships - Lumineau, Fabrice; Oxley, Joanne E. (Organization Science, 2012)
We examine how partners in vertical exchange relationships actually resolve disputes that are sufficiently serious to get lawyers involved. Reaching beyond the usual domain of organizational and management research, we leverage findings from law and economics to offer a novel organizational perspective on litigation and private dispute resolution, and we develop hypotheses about the likelihood of litigation in different exchange settings. Our empirical analysis generates three sets of new findings: First, counter to the received wisdom, we see that the involvement of lawyers does not necessarily signal the bitter end of an exchange relationship, because firms frequently manage to avoid litigation and resolve their disputes privately, and they do so in a manner that accords with our theoretical predictions. Second, we see that familiarity with exchange partners does not automatically lead to increased willingness to work things out; rather, our empirical results suggest that the impact of exchange duration on parties' willingness to resolve disputes privately is contingent on the development of norms of cooperation: in the event that such norms do not develop, the probability of a litigated outcome actually increases over time. Finally, we see that firms' willingness to work things out privately is also influenced positively by the shadow of the future. These findings are suggestive of a “discriminating alignment” between exchange characteristics and the choice of dispute resolution procedure, and they thus inject important new evidence into ongoing discussions about the legal underpinnings of different governance forms.